Educational doll design with exploration of the mechanical properties Khombouw bark - Utami, Putri Prabu; Suseno, Bayu Aji Suseno Aji; Astuti, Retnoning Adji Widi; Rinantanti, Yulini; Guspara, Winta Adhitia (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
The strategy for developing Khombouw bark craft products in Asei Village, Jayapura Regency, has not yet been optimized to become an interactive learning medium for forming early childhood interest in learning and building character education based on local Papuan wisdom. This research explores the mechanical properties by testing the bending strength of Khombouw bark material as a primary material for making character dolls for Papuan children. This research uses a Research and Development (R&D) development approach, including existing, archetype, and experimental studies. The process of assembling the prototype doll from Khombouw bark uses basic patterns with manual sewing techniques and is reinforced with composite materials to give a handmade impression. The results of this research show that natural fiber in the form of bark from the Khombouw tree has a high level of elasticity that can be applied in the design of volumetric product construction. Visualization of educational dolls using natural colors (wood brown or reddish brown) produced from the surface of Khombouw bark material, which is displayed on child figures by adapting the biological characteristics of Papuans (curly hair), as well as traditional clothing such as crowns, noken and tassels to build Papuan cultural identity.